Menstrual cycle tracking in professional volleyball athletes - Roffler, Andrea; Fleddermann, Marie-Therese; de Haan, Hanna; Krüger, Karsten; Zentgraf, Karen (Frontiers in Sports and Active Living, 2024)
Introduction The menstrual cycle may affect well-being and physical performance of elite female athletes by interfering with the function of multiple physiological systems. The aim of this study was to characterize the symptoms of the menstrual cycle and their frequency in elite female volleyball players. Methods Twenty professional female volleyball players were instructed to track their menstrual symptoms over the course of the first German national league season using the FitrWoman® tracking app. The app recorded the cycle length, duration, and intensity of the period as well as the occurrence and frequency of frequent cycle symptoms. The reported symptoms were then categorized into four categories (frequently, sometimes, rare, never) in order to create an individual Menstrual Symptom index (MSi) for each athlete. Results The most frequently occurring symptoms among all players without hormonal contraception (non-HC; n = 15) were “stomach cramps” (n = 15), “sleep disturbances” (n = 11), and “tiredness” (n = 11). The average number of symptoms counted per cycle was 11.8 (±17.7) and the average calculated MSi within the team was 12.9 (±10.7) points for non-HC users. The HC players (n = 4) also regularly experienced symptoms such as “sleep disturbances” or “tendered breasts”. The most common symptoms “stomach cramps” and “disturbed sleep” occurred more frequently during menstruation, while symptoms such as “bloating”, “cravings” or “tendered breasts” did also peak before menstruation. Discussion Menstrual cycle symptoms can be highly individual within a professional sports team. The calculation of the MSi seems to be a simple and accessible method to describe and overview the intensity and prevalence of symptoms in top female athletes in sports games.